PERBANDINGAN NILAI INDEKS CASTELLI RISK II PADA FAKTOR RESIKO STROKE ISKEMIK SERANGAN PERTAMA - Zenine Charolin Sinulingga; Rizaldy Taslim Pinzon; Loury Priskila; MMA Dewi Lestari (STIKES RS Baptis Kediri, 2026)
Background: Ischemic stroke is the most common type of stroke and a leading cause of disability and death. One of its major risk factors is dyslipidemia, which can be assessed using the Castelli Risk Index II (CRI-II), calculated as the ratio of LDL to HDL. A high CRI-II indicates increased atherogenic potential and a higher likelihood of stroke occurrence, particularly the first event. Objective: This study aims to determine the comparison of CRI-II values based on ischemic stroke risk factors such as hypertension, age, sex, diabetes mellitus, smoking status, and lipid profiles in patients with first-onset ischemic stroke. Methods: This was a descriptive analytic study using a cross-sectional approach and secondary data from 120 ischemic stroke patients aged 40–59 years across several hospitals in Yogyakarta. Data analysis was conducted using the Kolmogorov-Smirnov normality test and the chi-square test to assess relationships between variables. Results: Most patients (55%) had high CRI-II values (>3.5). No significant differences in CRI-II were found based on hypertension, age, sex, smoking status, or history of diabetes mellitus. However, there was a significant association between high LDL levels and CRI-II values (p=0.001), indicating the dominant role of LDL in increasing atherosclerotic risk, as LDL is directly involved in the CRI-II calculation. Conclusion: There were no significant differences in CRI-II values across most analyzed risk factors, except for LDL levels. This highlights the importance of lipid control, especially LDL, in preventing first-time ischemic stroke.